2021
DOI: 10.1097/wnr.0000000000001704
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Dimethyl malonate on neuroinflammation and blood-brain barrier after ischemic stroke

Abstract: Objectives After ischemic stroke, microglia will be activated and play a key role in neuroinflammation and the destruction of the blood-brain barrier (BBB), and activated microglia could polarize into pro-inflammation M1 phenotype and anti-inflammation M2 phenotype. Dimethyl malonate (DMM) could reduce reactive oxygen species and we speculate DMM could regulate microglia to protect ischemic brain. MethodsWe used transient middle cerebral artery occlusion (tMCAO) mouse model to simulate ischemic stroke and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Recent data has shown that succinate accumulates in both the human and mouse brain upon ischemia, and that inhibiting its oxidation via delivery of SDH inhibitors before stroke induction 31 or before stroke reperfusion 32 can lead to a dose-dependent decrease in brain injury.…”
Section: Previous Approaches Centred On the Detection Of Metabolic Al...mentioning
confidence: 99%
“…Recent data has shown that succinate accumulates in both the human and mouse brain upon ischemia, and that inhibiting its oxidation via delivery of SDH inhibitors before stroke induction 31 or before stroke reperfusion 32 can lead to a dose-dependent decrease in brain injury.…”
Section: Previous Approaches Centred On the Detection Of Metabolic Al...mentioning
confidence: 99%
“…6 Dimethyl malonate inhibits accumulation of SI, which prevents rapid oxidization of SI to form mitochondrial reactive oxygen species. Dimethyl malonate has been shown to protect several different tissue beds in the presence of ischemia-reperfusion, including the brain, 23,24 liver, 25 and perhaps most studied, the heart. 22,26,27 Whether DMM can be therapeutic after severe HS is unknown.…”
mentioning
confidence: 99%
“…Microglia are important in maintaining brain microenvironment homeostasis, and to a large extent, microglial activation contributes to the inflammatory response in the setting of stroke 27 . Therefore, we stained Iba1 at the peri‐infarction area to explore microglial activation.…”
Section: Resultsmentioning
confidence: 99%